Design and Workspace Optimization of 3-CPR Parallel Mechanism - Cheng Qiang; Li Ruiqin (Jixie chuandong)
A new kind of orthogonal 3-DOF 3-CPR parallel mechanism which can realize three-dimensional translation is proposed. The virtual prototype of 3-CPR mechanism is established,and the kinematics simulation experiment is carried out by using ADAMS software. The experiment shows the mechanism has good kinematics performance. The workspace of the mechanism is solved by using search method. The workspace volume of the mechanism is optimized by using genetic algorithm. The size parameters of the mechanism are obtained when the workspace volume takes the maximum value. The 3-CPR parallel mechanism has the advantages of simple structure,high stiffness,large output force,large workspace,and so on,because of using the prismatic pairs as the driving pairs. The results of the workspace optimization have important reference value for the application of the mechanism.